Associations of BCL-2 (RS17759659), CTLA-4 (RS231775), APO-1/FAS (RS2234767) genes polymorphisms with activity of proliferation and apoptosis in thyroid tissue of patients with nodular forms of goiter combined with autoimmune thyroiditis and thyroid adenoma - Sheremet, M. I.; Sydorchuk, L. P.; Shidlovskyi, V. A.; Bedenyuk, A. D.; Sydorchuk, R. I.; Gyrla, Y. V.; Bilookiy, O. V.; Tkachuk, N. P.; Kurochkin, G. S.; Levitsky, A. V. (Journal of Education, Health and Sport, 2017)
The study of apoptosis and proliferative activity in the thyroid gland (TG) tissue of patients with nodular goiter and autoimmune thyroiditis (NGAIT) and thyroid adenoma (TA) is based on the expression/density of Fas/FasL, BCL-2, p53, and Ki-67 markers assessment depending on the genetic polymorphisms of BCL-2 (rs17759659), CTLA-4 (rs231775) and APO-1/Fas (rs2234767) genes. Several mechanisms of thyroid cells’ programmed killing are activated in NGAIT and TA with domination of Fas-induced apoptosis, which strongly associates with the BCL-2 gene’s (rs17759659) promoter (F=25.33; p<0.001) and almost six fold weaker associates with the CTLA-4 gene’s (rs231775) promoter (F=4.23, p=0.017). Factors that decrease the likelihood of NGAIT and TA regardless of the CTLA-4 (rs231775) and APO-1/Fas (rs2234767) genes’ genotypes are the high Ki-67 density and reduction of cells containing p53 or BCL-2 proteins (OR=0.07-0.17; 95% CI OR: 0.03-0.36; p<0.001, and OR=0.08-0.11; 95% CI OR: 0.02-0.31; p<0.001, respectively). High expression of surface Fas and FasL in lymphoid infiltration and destruction of thyroid cells (stronger in GG-genotype carriers of the BCL-2 gene by 18.54% (pAA=0.043) and 36.18% (pAG=0.018), respectively) indicates the initiation of the external pathway of apoptosis through the caspase mechanism (effector caspase- 8).